Transparency Research of Banks of Lithuania - Titarenko, Jekaterina (Ekonomika, 2002)
Since banks in Lithuania are becoming more dependant on foreign capital, approaching integration into the European Union will even more force the migration of financial flows. Banking supervision authority of Lithuania (Bank of Lithuania) is coming across a serious problem on how to ensure stability of banking system when some elements of it cannot be thoroughly controlled. Under such circumstances the Bank of Lithuania, as the supervisal)’ authority, should rely on market potential to discipline banks and apply such supervisal)’ methods, which could force banks to operate in safe manner.The research of sensitivity of depositors of Lithuania’s banks towards the published information showed no reaction of the depositors to the information disclosed by banks during the period of 1997-2001. The indifference of the deposits lead to assume that the information disclosed by banks was not adequate, and (or) depositors were unable to properly interpret it. As such the potential of market discipline for ensuring the stability of the banking system was insufficiently used.In attempting to integrate market discipline elements into the model of banking supervision of Lithuania, the following is recommended:• to approve a legal act, regulating the purpose, policy and procedures of public disclosure of banks;• to oblige the Bank of Lithuania to regularly disclose information on the banking supervision functions and performance of the banking system.The application of the proposed elements should improve the information flows on the performance of banks, enhance the transparency of banks operations, encourage safe banking management and ensure market participants to monitor performance of banks and make greater influence thereon.